The Effect of Government Expenditure in the Education Sector, Human Development Index, and Economic Growth on Poverty Rate in Eastern Indonesia - Nefaorin Atara Sayyidina; Dicky Iranto; Suparno Suparno (Forum Kerjasama Pendidikan Tinggi, 2023)
This study aims to determine the effect of government expenditure in the education sector, human development index, and economic growth on poverty rates in Eastern Indonesia. The research method of this article is quantitative, with multiple linear regression analysis techniques. The data used in this study is secondary data obtained through the central statistics agency in the form of panel data from 13 provinces in Eastern Indonesia. The results stated that (1) government spending in the education sector did not have a significant effect on Poverty;(2) the human development index has a negative and significant effect on Poverty; (3) economic growth has a negative and significant effect on Poverty. The results of this study imply that direct subsidies or individual subsidies sourced from government spending in the education sector need to be targeted at low-income households. In addition, direct government spending on public services and infrastructure, especially in the welfare, health, and education sectors, is prioritized for low-income households to improve the human development index. This public investment transmission mechanism is one of the Government's efforts to accompany economic conditions towards Poverty and equal income distribution. Thus, it will reduce the poverty rate in Eastern Indonesia.